Wear-Resistant Ultrahigh-Molecular-Weight Polyethylene-Based Nano- and Microcomposites for Implants - S. V. Panin; L. A. Kornienko; N. Sonjaitham; M. V. Tchaikina; V. P. Sergeev; L. R. Ivanova; S. V. Shilko (Journal of Nanotechnology, 2012)
The influence of modification by hydroxyapatite (HA) nano- and microparticles on tribotechnical properties of ultrahigh-molecular-weight polyethylene (UHMWPE) was investigated to develop polymer implants for endoprosthesis. It was shown that modification of UHMWPE by hydroxyapatite nanoparticles within range of 0.1–0.5 wt.% results in increase of wear resistance at dry sliding by 3 times. On the other hand adding of 20 wt.% of micron size HA gives rise to the same effect. The effect of increasing wear resistance is not substantially changed at surface treatment of the nano- and microcomposites by N+ ion beams as compared with nonirradiated blends. Preliminary joint mechanical activation of UHMWPE powder and fillers results in more uniform distribution of nanofillers in the matrix and, as a result, formation of more ordered structure. Structure within bulk material and surface layers was studied by means of optical profilometry, scanning electron microscopy, infrared spectroscopy, and differential scanning calorimetry. It is shown that adding of hydroxyapatite nanoparticles and high-energy surface treatment of the composite by N+ ion implantation improve tribotechnical properties of UHMWPE due to formation of chemical bonds in the composite (crosslinking) and ordering of permolecular structure.